ANALISIS ONE-MINUTE PAPER DALAM PEMBELAJARAN MEMBACA PUISI SISWA KELAS VIII SMP MUHAMMADIYAH 23 KEDUNGPRING - Okta Diana Anggrayni; Syamsul Sodiq; Miftachul Amri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Assessment is the process of collecting and assessing information to evaluate students' understanding, skills, and development in various aspects of learning. This study aims to analyze One-Minute Paper (OMP) as an assessment model in learning to read poetry in grade VIII of SMP Muhammadiyah 23 Kedungpring. The background of this research is based on the limited assessment instruments that are able to record the reflective and affective aspects of students in literary learning, especially poetry. The approach used is descriptive qualitative by involving OMP sheets and performative observations as the main instruments. The results of the analysis show that OMP is able to explore the understanding of the meaning of poetry, foster emotional involvement, and encourage students' reflective thinking skills. Students show an interest in poems that contain strong imagery and symbolic meaning, and begin to build a personal relationship with the text. In addition, observations of reading performance show that there are developments in the aspects of fluency, intonation, articulation, expression, and student participation in the classroom